K-pop TikTok: TikTok's expansion into South Korea, TikTok Stage, and platformed glocalization - Abidin, Crystal; Lee, Jin (2023)
We examine how TikTok expanded into the South Korean landscape by utilizing K-pop as a vehicle, thus demonstrating the theory of ‘platformed glocalization’. After several failed attempts to enter the Korean market – having been stigmatized as a ‘vulgar Chinese app’ – TikTok Korea eventually launched a successful event series known as ‘TikTok Stage’ to leverage on the gaps in the K-pop market arising from the COVID-19 pandemic. While ‘platformization’ has been studied as the pervasive reach and impact of platforms on cultures, we showcase the potential for a variant that we term ‘platformed glocalization’, usually observed when domestic market cultures and their associated socio-politics are particularly strong. We investigate K-pop stars and fans’ ‘promotional labour’ during the events, which is essential in the process of platformed glocalization. We discuss how the mainstream entertainment industry and newly emerging social media platforms work in tandem to produce a market-specific mobilization of digital cultures.